A successful approach by a small university to transportation management: A case study of Northeastern University, Thailand - Buntornwon, Theenida; Kumphong, Jetsada (Universitas Diponegoro, 2022)
Sustainability is a necessary consideration for ensuring quality of life for current and future generations. It is an absolute priority of Northeastern University (NEU), Khon Kaen, that both operational and academic efforts remain focussed towards delivering a positive impact on the natural world in both the immediate environment and beyond. The university has been a proud participant in the UI Green initiative since 2016 and has seen its green credentials rise significantly thanks to the collaborative efforts of staff – from the board of directors to academic, professional and operational staff – and both current and past students. The purpose of this paper is to highlight the practices of Northeastern University in relation to transportation management; a field in which the university has received the highest rating across six applicable green measurement metrics. By using time series analysis, we expect that this initiative will allow the university to achieve even higher scores by 2022. As a private university with a select student and staff base, the university aims to make efficiency savings wherever possible; however, these aims are aligned with the university’s green initiatives, rather than working in conflict with them. The university has an absolute commitment to reducing CO2 emissions, increasing renewable energy usage, and lessening carbon footprints on both an individual and institutional level.Keyword: NEU, sustainability, CO2 emission, renewable energy